Cross-Mediterranean Egyptian migrants: a discursive analysis - Hussein, Sara (AUC Knowledge Fountain, 2019)
This thesis investigates how the Egyptian migrant subject who chooses to cross the Mediterranean through irregular means to reach Europe is discursively constructed in Egyptian media, particularly in the wake of the 2016 Rashid boat sinking. In both official and public discourse, this highly visible and well-documented accident raised questions on accountability and the role of the state in this situation. By identifying and analyzing the themes represented throughout a diverse collected fieldwork corpus of various Egyptian media, statements by public officials and organizations, newspaper articles and editorials, television talk show programming, and popular cultural production, this thesis offers a lens to study the dynamics of Egyptian irregular mobility. This research uses critical discourse analysis to examine the ways in which these individuals have been represented by hegemonic narratives linking them to the material conditions of socio-economics and wider securitization policy that shape the production of knowledge on this issue.